3(4x² -y² )-5(4x² +4xy+y² ) :)

I done the 1st step which is 3(2x+y)(2x-y)-5(2x+y)²

(2x+y)(3(2x-y))-5(2x+y)

but then i cant facortise anymore after i take out the (2x+y)

Printable View

- November 19th 2008, 02:04 AMhelloyingfactorise
3(4x² -y² )-5(4x² +4xy+y² ) :)

I done the 1st step which is 3(2x+y)(2x-y)-5(2x+y)²

(2x+y)(3(2x-y))-5(2x+y)

but then i cant facortise anymore after i take out the (2x+y) - November 19th 2008, 03:07 AMMath_Helper
3(2x+y)(2x-y)-5(2x+y)²=(2x+y)[3(2x-y)-5(2x+y)]=(2x+y)[6x-3y-10x-5y]=

=(2x+y)[-4x-8y]=-4(2x+y)(x+2y)